Pengaruh Pajak Bumi Bangunan, Bea Perolehan Hak Atas Tanah Dan Bangunan Terhadap Pendapatan Asli Daerah Kabupaten Sumenep - Nasrullah Wahyu Maulana; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
In this era of globalization, economic growth is increasingly rapid. As an effort to improve people's welfare based on justice and prosperity which are the goals of national development, the Indonesian economy will also be followed by policies in the tax sector. 1. Based on the background of the problem above, the problem can be formulated as follows: Does PBB and BPHTB revenue have an effect on PAD in Sumenep Regency? 2. Does PBB revenue have a significant effect on PAD in Sumenep Regency? 3. Does BPHTB revenue have a significant effect on PAD in Sumenep Regency?. From the results of the data analysis and discussion that have been described, the following conclusions can be drawn: 1. The influence of PBB's contribution to PAD in Sumenep Regency 2013-2022. Where PBB partially has a positive and significant effect on PAD with a calculated T value of 28.518 and a significance level of 0.000 < 0.05. 2. Influence of BPHTB Contribution to PAD of Sumenep Regency 2013-2022. Where BPHTB partially has a positive and significant effect on PAD with a calculated T of 2.318 and a significance level of 0.000 <0.05. 3. Effect of PBB Contribution, BPHTB on PAD of Sumenep Regency 2013-2022, Based on the results of the F test simultaneously the PBB contribution variable and the BPHTB contribution variable have a positive and significant effect on PAD with an F table value of 2113.398 > 3.16 and a Sig. 0.000 < α = 0.05.